Toward better understanding the corporate innovation landscape in New Zealand using Industrial Research Ltd's "What's your problem New Zealand?": Competition data: analysis and propositions - Campbell, Charles; Cummings, Stephen; Daellenbach, Urs; Davenport, Sally (School of Management Working Papers, 2011)
This paper utilises a unique data set to investigate New Zealand’s corporate innovation landscape. It examines a sample of kiwi firms with true “innovative intent”, and their efforts to gain external R&D support from Industrial Research Limited (IRL), a Crown Research Institute. Aggregated data from over 100 applications to IRL’s “What’s Your Problem New Zealand?” competition, held in 2009, informs of these companies’ location, size, age, export orientation, sector, and research problem type. We divide the competition entrants into three categories: “strayers”, “contestants”, and “finalists”, and consider their aforementioned characteristics in relation to each other and, where possible, to the median New Zealand firm. From this, we advance 14 propositions regarding the nation’s corporate innovation landscape, and suggest some potential implications for policy makers.